The Association between Obesity and Depression among Children and the Role of Family: A Systematic Review - Aikaterini Kanellopoulou; George Antonogeorgos; Konstantinos Douros; Demosthenes B. Panagiotakos (MDPI AG, 2022)
One of the most critical factors that affects or leads to obesity is depression. However, another point of view is that obesity leads to depression. This systematic review estimates evidence arising from observational and systematic studies concerning the association between obesity and depression in children and adolescents. Moreover, the role of the family environment is investigated in this review. A systematic literature search was performed for research conducted between 2014 and 2021 on PubMed. The basic inclusion criteria were the language, study issue and type, and age of the participants. Studies that examined non-healthy populations, or were not related, or with no access were excluded. Titles and abstracts were screened independently, and full-text manuscripts meeting inclusion criteria were extracted. Finally, twenty-seven studies were retained. Most of them highlighted a positive association between obesity and depression. However, it is not clear whether obesity leads to depression or vice versa. Our review also revealed that the role of the family in this association has not been well studied and understood, since only one study addressed the issue. The evidence from our review emphasizes major public health issues; therefore, appropriate health policies should be developed. Moreover, additional research is required to fully understand the role of the family environment in the association between depression and obesity in childhood.